False Identification Signature Analysis Method With Error Sum Squared (SSE) - Purniyawati S; Vandika A Y (Bandar Lampung University (UBL), 2017)
Today the level of falsification of signatures is very common. Perpetrators are often categorized based on the quality of the crime, and the motive of his actions. In falsifying signatures actors also have special characteristics that make it distinguishable from each other. Perpetrators forged the signatures of his actions as 'fine' so unknowingly carry have become victims of crime. The signature is one that is widely used biometric humans. Signature also special of handwritten forms that contain special characters and additional forms are often used as proof of identity verification of a person. In the process of identifying the signatures still done scientifically by matching signatures, but how did the introduction of a signature using a computer viding a challenge until now, because the form of a signature unique to each person. Differences signature manually can be seen from the hassle pattern used by the owner. Some sample signature of each person are generally identical, but not really thesame. Signature of person often change over time, usually in terms of position and size of the signature. Usually a signature is used as the primary mechanism to authenticate and authorize the transaction legal. And can also be used to identify one person to another. Based on the description above, this research is expected to help in reducing the crime rate in the use of signatures.